ANALISIS FAKTOR INTERN YANG MEMPENGARUHI HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS SMA TAMAN MULIA KUBU RAYA - Natalia, Yulia Krista Intani; Aminuyati, Aminuyati; Khosmas, F. y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This thesis is entitled "Analysis of Internal Factors Affecting Student Learning Outcomes in Economics Subject Class XI PS SMA TAMAN MULIA Kubu Raya". The method used is descriptive method. The form of the research is qualitative description. The data collection techniques in this study were: distributing questionnaires via google from and observing and collecting school data. With the results of the study as follows: 1) Analysis of internal factors that affect learning outcomes. Based on the results of research on indicators of learning attitudes in general, learning attitudes are quite good and learning attitudes are good in understanding and doing the tasks given by the teacher 2) analysis of internal factors that affect learning outcomes at SMA TAMAN MULIA Kubu Raya. Based on the results of research on indicators of interest in learning in general In general, they are also good at answering questions given by the teacher. 3) students' learning motivation that affects learning outcomes. From the analysis of the discussion of indicators of learning motivation, it is quite good, it can be seen that students tend to be happy in solving problems on questions. In the learning process it is very important for a teacher to pay attention to his students in the learning process, the teacher must also see the learning attitude of students, student interest in the learning process and student motivation which is very important in achieving a goal.